Electrodeposited n-type cuprous oxide cubic nanostructures for liquefied petroleum gas sensing - Jayasingha, J. L. K.; Jayathilaka, K.M.D.C.; Gunewardene, M. S.; Dissanayake, D.P.; Jayanetti, J. K. D. S. (My University, 2016)
A surfactant free template assisted electrodeposition method was used to fabricate thick n-type Cu2O films having cubic nanostructures for the detection of liquefied petroleum (LP) gas at low concentrations. Templates were fabricated by initially electrodepositing a p-type Cu2O thin film on a Ti substrate followed by annealingthat changed conductivitytype ofthefilm, as confirmed by Mott–Schottky and spectral response measure ments. SEM measurements of resultingfilms showed nano-cubic crystals having sizes of 150–300 nm.When exposed to a mixture of LP gas and dry air, the resistance of these films increased and the maximum response was recorded when films were maintained at 180 8C for all concentrations and it was independent of the surface morphology. At 180 8C, at the lowest tested LP gas concentration of 2 vol.%, a twofold increase in response was observed in the nano-cubic films compared to the micro-crystalline n-type Cu2O films. This improvement in gas response is attributed to increased effective surface area of these nanostructured films. Compared to other LP gas sensing materials, Cu2O films showed very good response times and recovery times of 120 and 90 s, respectively
Keywords: Cu2O; Electrodeposition; gas; Hydrocarbons; Liquefied Petroleum; nanocubes; sensing; Thin films